Default mode network-basal ganglia network connectivity predicts the transition to postherpetic neuralgia - Ying Wu; Chao Wang; Wei Qian; Lieju Wang; Lina Yu; Minming Zhang; Min Yan (IBRO Neuroscience Reports)
Background: Neuroimaging studies have revealed aberrant network functional connectivity in postherpetic neuralgia (PHN) patients. However, there is a lack of knowledge regarding the relationship between the brain network connectivity during the acute period and disease prognosis. Objective: The purpose of this study was to detect characteristic network connectivity in the process of herpes zoster (HZ) pain chronification and to identify whether abnormal network connectivity in the acute period can predict the outcome of patients with HZ. Methods: In this cross-sectional study, 31 patients with PHN, 33 with recuperation from herpes zoster (RHZ), and 28 with acute herpes zoster (AHZ) were recruited and underwent resting-state functional magnetic resonance imaging (fMRI). We investigated the differences in the connectivity of four resting-state networks (RSN) among the three groups. Receiver operating characteristic (ROC) curve analysis was performed to identify whether abnormal network connectivity in the acute period could predict the outcome of patients with HZ. Results: First, we found within-basal ganglia network (BGN) and default mode network (DMN)-BGN connectivity differences, with PHN patients showing increased DMN-BGN connectivity compared to AHZ and RHZ patients, while RHZ patients showing increased within-BGN connectivity compared to AHZ and PHN patients. Moreover, DMN-BGN connectivity was associated with the ID pain score in patients with AHZ. Finally, the DMN-BGN connectivity of AHZ patients could predict the outcome of HZ patients with sensitivity and specificity of 77.8 % and 63.2 %, respectively. Conclusions: Our results provide evidence that DMN-BGN connectivity during the acute period confers a risk for the development of chronic pain and can act as a neuroimaging biomarker to predict the outcome of patients with HZ.